Correlation between Body Mass Index and Central Adiposity with Pregnancy Complications in Pregnant Women - Mehrangiz Ebrahimi-Mameghani; Esmat Mehrabi; Mahin Kamalifard; ParisaYavarikia (Tabriz University of Medical Sciences, 2013)
Background: The prevalence of obesity is increasing throughout the world. Obesity assessed by body mass index (BMI) has shown to be associated with gestational complications while the relationship using waist circumference (WC) is not clear yet. The present study was aimed to determine the relationship be-tween WC and adverse pregnancy complications.Methods: In this prospective cohort study, 1140 nulliparous pregnant women at 1st trimester of pregnancy referred to health care centers in Tabriz, Iran were enrolled in 2009-2010. Anthropometric indexes including (weight, height and WC) were measured using standardized measures and methods. BMI was clas-sified into normal, overweight and obesity based on WHO classification. Ab-dominal obesity was defined as WC ≥ 88 cm. Pregnancy complication including gestational diabetes, hypertension and preeclamsia. Data were analyzed using SPSS, version 16.Results: Mean of BMI and WC were 24.32±4.08 kg/m2, 81.84±9.25cm at 1st trimester of pregnancy, respectively. Prevalence of overweight (BMI=25-29.9 kg/m2) and obesity (BMI>29.9 kg/m2) was 27.6%, 8.8%, respectively. Abdo-minal obesity based on WC was 34.8%. Significant correlations were found between BMI and WC (r=0.73, P =0.0001). Women with BMI>29.9 kg/m2 and WC>88 cm were more likely to suffer from gestational pregnancy and hyper-tension, as well as preeclampsia and preterm delivery.Conclusion: Early maternal WC similar to BMI is related with pregnancy complications.